Molecular insights into arabidopsis response to Myzus persicae sulzer (green peach aphid) - Pegadaraju, Venkatramana (Kansas State University, 2005)
Phloem-feeding insects like aphids feed on a variety of crop plants and limit plant productivity. In addition they are vectors for important plant viruses. Efforts to enhance plant resistance to aphids have been hampered by lack of sufficient understanding of mechanisms of plant defense against aphids. I have utilized a plant-aphid system consisting of the model plant Arabidopsis thaliana and the generalist aphid, Myzus persicae Sulzer (green peach aphid [GPA]), to study plant response to aphids. These studies have demonstrated an important role of premature leaf senescence in controlling aphid growth in Arabidopsis. Molecular and physiological studies suggest that the Arabidopsis PAD4 (PHYTOALEXIN DEFICIENT 4) gene modulates the GPA feeding-induced senescence process. Furthermore, in comparison to the wild type plants, GPA growth was higher on pad4 mutant plants, suggesting an important role for PAD4 in plant defense against GPA. In contrast, constitutive expression of PAD4 in transgenic Arabidopsis enhanced basal resistance against GPA. Unlike its involvement in plant defense against pathogens, the role of PAD4 in Arabidopsis resistance to GPA is independent of its involvement in phytoalexin biosynthesis and of its interaction with EDS1, a PAD4-interacting protein. Instead, the heightened resistance to GPA in these PAD4 constitutively expressing plants was associated with the rapid activation of leaf senescence. The association of premature leaf senescence in basal defense against GPA is supported by our observation that in comparison to the wild type plant, GPA growth was restricted on the Arabidopsis hypersenescence mutants, ssi2 and cpr5. Gene expression studies suggested some overlap between plant responses to pathogens and aphids, for example, activation of genes associated with the salicylic acid (SA) signaling pathway. However, the characterization of aphid performance on Arabidopsis SA biosynthesis and signaling mutants have ruled out the involvement of SA signaling in controlling aphid growth.
Keywords: Senescence; Phytoalexin; Arabidopsis; Green peach aphid; Microarray; Cell death; Biology, Molecular (0307)